2012
DOI: 10.1074/jbc.m112.350108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction of Sclerostin with the Low Density Lipoprotein Receptor-related Protein (LRP) Family of Wnt Co-receptors

Abstract: Background: Sclerostin, an inhibitor of Wnt signaling, binds to the ␤-propeller domain-containing Wnt co-receptors LRP6 and LRP4. Results: An NXI motif in sclerostin mediates interactions with LRP6 (but not LRP4) and blocks Wnt1 signaling. Conclusion:The sclerostin/LRP6 interaction shares features with the well characterized nidogen/laminin interaction. Significance: NXI motifs are important in mediating interactions with ␤-propeller containing proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 45 publications
(53 reference statements)
7
89
0
Order By: Relevance
“…30 The Wnt3a class encompasses Wnt3 and 3a and binds b-propeller 3 of LRP5/6. 30 Interestingly, sclerostin has been shown to inhibit the Wnt1 class by binding to the first b-propeller region of LRP5/6 but not the Wnt3a class, 24,30,31 which is coherent with our result. The fact that sclerostin could inhibit BMP2-or Wnt3a-induced osteoblast differentiation without antagonizing their respective canonical signaling suggested that it could function through another signaling pathway.…”
Section: Discussionsupporting
confidence: 91%
“…30 The Wnt3a class encompasses Wnt3 and 3a and binds b-propeller 3 of LRP5/6. 30 Interestingly, sclerostin has been shown to inhibit the Wnt1 class by binding to the first b-propeller region of LRP5/6 but not the Wnt3a class, 24,30,31 which is coherent with our result. The fact that sclerostin could inhibit BMP2-or Wnt3a-induced osteoblast differentiation without antagonizing their respective canonical signaling suggested that it could function through another signaling pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Its role in negatively regulating bone mass is exemplified by naturally occurring SOST loss-of-function mutations in humans, which cause the severe bone overgrowth disorders sclerosteosis [Mendelian Inheritance in Man (MIM269500)] (3,4), van Buchem disease (VBD) (MIM) 239100 (3,5,6), and craniodiaphyseal dysplasia (CDD) (MIM 122860) (7). Sclerostin inhibits WNT/β-catenin signaling, considered as canonical WNT signaling by binding to WNT coreceptors LRP5 and LRP6 (8)(9)(10)(11)(12)(13)(14)(15), thereby disrupting the formation of a WNT1-type ligandreceptor complex (9,11,12). In addition, we recently identified a facilitator of sclerostin action, the low-density lipoprotein receptor-related protein (LRP) family member LRP4.…”
mentioning
confidence: 99%
“…For the C-terminal part of Dkk1 the binding to ␤ -propeller III involves similar residues, except the residues corresponding to Asn(1082), as if binding an NxI motif, although no NxI motif was seen in this part of Dkk1 ( 10,11 ). Furthermore, it has been elegantly demonstrated by Holdsworth et al that sclerostin also binds its cognate receptors LRP5 and LRP6 via its NxI motif ( 64 ). Moreover, as LRP2 contains three ␤ -propellers with an SBiN motif, it is interesting that an analysis of the sequences of known LRP2 ligands reveals that cubilin, vitamin D-binding protein, transcobalmin-vitamin B12, serum albumin, and apoB all contain one or two copies of exposed NxI motifs, although LRP2 binding using this motif has not yet been shown.…”
Section: Biological Implications Of Protein Interactions Of the Lrp ␤mentioning
confidence: 98%